Signifikansi Tata Liturgi terhadap Keterlibatan Umat Menghadirkan Pembaharuan Hidup di Generasi Masa Kini - Rusmanto, Ayub; Gozaly, Ricky; Naftali, Joseph (Sekolah Tinggi Teologi Kalvari Manado, 2024)
Abstract: Liturgy is a procedure of worship agreed upon and carried out by the church with the aim of worship in the church running smoothly and structured. The significance of liturgy in Christianity manifests God's encounter with the people so that the role of the church in facilitating the liturgy of worship involves the people presenting the renewal of the life of today's generation. The renewal of the lives of the younger generation as concrete evidence is carried out in worship to celebrate and be grateful for the work of salvation that God has done. Ironically, some churches today do not carry out liturgy well. The church does not facilitate well the